2020
DOI: 10.1016/j.mbs.2020.108323
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic dynamics in a time-delayed model for autoimmunity

Abstract: Article (Accepted Version) http://sro.sussex.ac.uk Fatehi, Farzad, Kyrychko, Yuliya N and Blyuss, Konstantin B (2020) Stochastic dynamics in a time-delayed model for autoimmunity. Mathematical Biosciences, 322. a108323.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 109 publications
(167 reference statements)
0
5
0
Order By: Relevance
“…It would be interesting and important to investigate how (in)stability of extinction steady state is affected by stochasticity, and how it impacts the regimes of bi-stability between extinction and other equilibria. This could be achieved through numerical exploration of basins of attraction of different steady states in the stochastic model in a manner similar to how it was done by Fatehi et al [47,48] in the context of modelling autoimmunity arising from immune response to a viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting and important to investigate how (in)stability of extinction steady state is affected by stochasticity, and how it impacts the regimes of bi-stability between extinction and other equilibria. This could be achieved through numerical exploration of basins of attraction of different steady states in the stochastic model in a manner similar to how it was done by Fatehi et al [47,48] in the context of modelling autoimmunity arising from immune response to a viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, earlier work of Iwami et al [10,11] has shown that, while this behaviour can be observed for both types of growth functions in the absence of infection or immune reaction, their specific functional form does have a significant effect on the overall dynamics of autoimmune disease. Thus, we have chosen to use a logistic form for the growth function of healthy organ cells, in agreement with Iwami et al [10] and our earlier work on autoimmunity [34][35][36][37][38][39][40].…”
Section: Deterministic Mathematical Modelmentioning
confidence: 91%
“…Blyuss and Nicholson [34,35] used a TAT-based model to investigate autoimmunity arising through a mechanism of molecular mimicry from immune response to a viral infection. To capture a dynamical regime where autoimmunity arises as a by-product of viral infection but after that initial infection has already been cleared by the immune system, Fatehi et al [36][37][38][39][40] developed this model further by including cytokines mediating T cell proliferation, as well as time delays associated with various aspects of the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…at order Ω 0 one obtains a delayed Fokker-Planck equation that describes stochastic oscillations around the deterministic trajectory (see Appendix A). Following the methodology of Galla 60 (see also [61][62][63][64] ), we can use this delayed Fokker-Planck equation to obtain the following system of Langevin equations describing the dynamics of fluctuations around a deterministic steady state (u * , v * ) of the model ( 2)…”
Section: Stochastic Modelmentioning
confidence: 99%
“…while for stochastic systems without time delay one could use a Lyapunov equation to obtain the covariance matrix 61,66,67 . The level of fluctuations around the dominant spectral frequency for each of the two populations X u (t) and X v (t) around their steady-state values X * u and X * v can be quantified using their respective mean-square variances…”
Section: Stochastic Modelmentioning
confidence: 99%